(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Osteoarthritis is a common and very devastating disease that affects one or both knees. The aim of the study was to assess the post-operative pain management of patients undergoing for TKR. Methodology: The current study design was cross-sectional descriptive that was conducted in 5 private and public sector hospitals of Rawalpindi and Islamabad. The total sample size were 60 nurses who deal patients of TKR from 1st April to 5th July 2022 using universal sampling technique. A self-structured tool was used for data collection, while data where analyzed through SPSS 20. The aim and objectives of the study was explained to each participant while data was collected after informed consent. Results: The findings revealed that majority of the patients 51 (56.7%) among 90 patients undergone for TKR were observed for pharmacological pain management in post-op period that received combined anesthesia through spinal and epidural. There were no pain assessment scale used for the assessment of pain during post-operative management and nor any nursing led pharmacological intervention were used observed in the study findings. Conclusion: The study concluded on the basis of findings that it is necessary for nurses and orthopedic team that a standardized protocol in care should be used for the pain assessment during post-operative phase. The standard care will not only help in fast recovery but will also promote patient satisfaction, reduction of risk from infection and cost effective.